THE SYMBOLIC SPACE: ESSENCE AND SUBJECTS OF FORMATION - Гон, М. М. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Idea, 2019)
The article investigates the symbolic space of towns. It is interpreted as reflecting collective memory; it is artificial by its essence, because it reflects the historical policy of the state and memory policy implemented by the state, on the one hand, and values of political elites and non-government organizations on the other hand. The “borders” of symbolic spaces of towns in one state are mostly similar, because they are defined by political, and social and cultural values, which the citizens of this state have. Based on the common connecting ideas, the symbolic spaces of cities at the same time can reflect regionalism. It is the result of the process when the territories, which were earlier the parts of other states, enter the given state. The competition for the collective memory between different social groups influences the symbolic space of towns. Nations can be the subjects of such competition. The results of this competition to large extent depend on the political culture of the participants. The author considers the factor of resource (in particular, governmental and human) to be an essential condition for the victory in this competition.